THE ADJUVANT USE OF CONSCIOUS SEDATION WITH NITROUS OXIDE IN ODONTOPHOBIC PATIENTS AT THE UNIVERSITY DENTAL CLINIC OF THE INTA-UNINTA UNIVERSITY CENTER - Nogueira, Luís Henrique dos Santos; de Oliveira, Michelly Silva; Pedroza, Ana Cristina Bevilaqua Batista; de Sousa, Luzia Hermínia Teixeira; Ponte, Raphaelle Menezes da Frota; Júnior, José Carlos Silva; Macedo, Sarah Mendes de Sousa; Costa, Kilvio Meneses; Diógenes, Hélvia Menezes Vasconcelos; Furtado, Manuela Almeida Montenegro; Mota, João Victor Taumaturgo; Nogueira, Karina Francischelli (Seven Editora, 2024)
Anxiety and odontophobia represent significant barriers in the daily life of dental surgeons, directly impacting the quality and success of care. These conditions manifest at different levels and require varied management strategies, such as behavioral techniques, pharmacological sedation, and other complementary approaches. Overcoming such challenges is essential not only for the benefit of the patient, but also for the improvement of the professional’s clinical practice. The present study aimed to evaluate the efficacy of conscious sedation with nitrous oxide (N₂O) in reducing anxiety and odontophobia in patients undergoing dental procedures. Five consultations were performed with conscious sedation in patients previously diagnosed with odontophobia. For the analysis, two evaluative instruments were applied: the Corah Dental Anxiety Test, used to measure anxiety levels before and after care, and the Trieger Test, used to assess changes in motor coordination resulting from sedation. In addition, vital signs, symptoms, and complications during the procedures were recorded and systematized for analysis. The results indicated that there were no significant changes in the Trieger Test scores before and after the consultations, suggesting that conscious sedation with nitrous oxide did not compromise the motor coordination of the patients. Stabilization or reduction of blood pressure was observed during the procedures, in addition to a noticeable reduction in anxiety levels, according to the data from the Corah Test. However, the intensity of odontophobia was shown to be associated with the complexity of the procedures performed. We conclude that the use of conscious sedation with nitrous oxide was effective in reducing anxiety in dental procedures, reinforcing its role as an adjuvant tool in the management of odontophobic patients. However, the results did not allow us to establish significant correlations between anxiety, age, or gender of the patients. DOI:https://doi.org/10.56238/sevened2024.037-055